Metformin Overcomes Acquired Resistance to EGFR TKIs in EGFR-Mutant Lung Cancer via AMPK/ERK/NF-κB Signaling Pathway - Li, Ling; Wang, Tao; Hu, Mengdi; Zhang, Yali; Chen, Hongzhuan; Xu, Lu (Frontiers in Oncology, 2020)
Background: The major limitation of EGFR TKIs in EGFR-mutant lung cancer therapy is the development of acquired resistance. The underlying mechanisms remain unknown in about 30% of cases. NF-kB activation was encountered in the acquired resistance to EGFR TKIs. Unfortunately, none of NF-kB inhibitors has been clinically approved. The most commonly used antidiabetic drug metformin has been demonstrated anti-tumor effects associated with NF-kB inhibition. Therefore, in this study, metformin was examined for its anti-tumor and anti-resistance effects and underlying mechanisms. Methods: In vitro and in vivo EGFR-mutant lung cancer models with acquired resistance to EGFR TKIs were used. Results: We found that NF-kB was activated in EGFR-mutant lung cancer cells with acquired resistance to EGFR TKIs. Metformin inhibited proliferation and promoted apoptosis of lung cancer cells, especially those with acquired EGFR TKI resistance. Moreover, metformin reversed and delayed acquired resistance to EGFR TKIs as well as suppressed cancer stemness in EGFR-mutant lung cancer. Mechanistically, those effects of metformin were associated with activation of AMPK, resulting in the inhibition of downstream ERK/NF-kB signaling. Conclusions: Our data provided novel and further molecular rationale and preclinical data to support combination of metformin with EGFR TKIs to treat EGFR-mutant lung cancer patients, especially those with acquired resistance.